Barriers to utilization of postnatal care at village level in Klaten district, central Java Province, Indonesia - Probandari, Ari (BMC Health Serv Res, 2017)
BACKGROUND: Maternal health remains a persisting public health challenge in Indonesia. Postnatal complications, in particular, are considered as maternal health problems priority that should be addressed. Conducting adequate care for postnatal complications will improve the quality of life of mothers and babies. With the universal health coverage implementation, the Indonesian government provides free maternal and child health services close to clients at the village level, which include postnatal care. Our study aimed to explore barriers to utilization of postnatal care at the village level in Klaten district, Central Java Province, Indonesia. METHODS: A qualitative study was conducted in March 2015 – June 2016 in Klaten district, Central Java, Indonesia. We selected a total of 19 study participants, including eight mothers with postnatal complications, six family members, and five village midwives for in-depth interviews. We conducted a content analysis technique on verbatim transcripts of the interviews using open code software. RESULTS: This study found three categories of barriers to postnatal care utilization in villages: mother and family members’ health literacy on postnatal care, sociocultural beliefs and practices, and health service responses. Most mothers did not have adequate knowledge and skills regarding postnatal care that reflected how they lacked awareness and practice of postnatal care. Inter-generational norms and myths hindered mothers from utilizing postnatal care and from having adequate nutritional intake during the postnatal period. Mothers and family members conducted unsafe self-treatment to address perceived minor postnatal complication. Furthermore, social power from extended family influenced the postnatal care health literacy for mother and family members. Postnatal care in the village lacked patient-centered care practices. Additionally, midwives’ workloads and capacities to conduct postnatal information, education and counseling were also issues. CONCLUSIONS: Despite the government’s efforts to provide free postnatal care closer to mothers’ homes, other barriers to postnatal care utilization remained. Specifically, among mothers, community, and health services. An innovative approach to increase the health literacy on postnatal care is required. In particular, improving the capacity of midwives to conduct patient-centered care. In addition, village midwives’ tasks should be evaluated and reoriented. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-2490-y) contains supplementary material, which is available to authorized users.